Vitamin E does not reduce the side-effects of isotretinoin in the treatment of acne vulgaris - (:unkn) unknown (WILEY, 2005)
Background Isotretinoin is widely used in the treatment of severe, recalcitrant, nodular acne. Mucocutaneous side-effects are seen in the great majority of patients and some of them have elevations in their serum lipid and liver enzyme profiles. Recently, it has been shown that addition of vitamin E decreased the toxicity of high-dose retinoids. Objective The purpose of this investigator-blinded, randomized study was to assess whether vitamin E would reduce the side-effects of isotretinoin in the treatment of acne vulgaris. Methods Eighty two patients were randomly assigned to one of two treatment groups with isotretinoin (1 mg/kg/day) alone or combined with vitamin E (800 IU/day). The treatment duration was 16 weeks. Mucocutaneous side-effects such as facial erythema, facial dryness, cheilitis and serum lipid and liver enzyme profiles were assessed. Results There was no difference in the incidence and severity of side-effects related to isotretinoin between the two treatment groups. Conclusion Eight hundred IU/day vitamin E did not improve the side-effects of 1 mg/kg/day of isotretinoin in the treatment of acne vulgaris.
Keywords: 13-CIS-RETINOIC ACID; ALPHA-TOCOPHEROL; PHASE-II; INTERFERON; TRIAL; CARCINOMA; TOXICITY